Implicaciones del uso de buscadores en el comportamiento de compra online - Carla Ruiz Mafé; Silvia Sanz Blas (Investigaciones Europeas de Dirección y Economía de la Empresa (IEDEE), 2009)
This paper aims to analyze the factors influencing the use of search engines and its impact on e-shopping behaviour. Analysis of the results obtained from a sample of 485 Spanish Eshoppers shows that consumers who value convenience, price reductions and wide assortment as motivations for purchase online are more likely to use search engines for e-shopping that those who do not. Online use experience and online shopping experience are negative key drivers of search engine use for E-shopping. Regarding implications, search engine use has no influence on online spending.
Keywords: 330; E-commerce; shopping orientations; search engines; consumer behaviour